2021
DOI: 10.33222/juara.v6i1.1164
|View full text |Cite
|
Sign up to set email alerts
|

Students’s Academic Level Stress During Online Learning in Physical Education

Abstract: Changes in online learning, especially in physical education learning, make students feel pressured by the assignments given by the teacher. This study aims to reveal the level of academic stress of students at each level starting from elementary, junior high and high school students when doing online learning of physical education. Survey research was used to uncover this problem. The population consisted of 76 elementary students, 88 junior high school students and 81 high school students scattered in Cimahi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
6
0
2
Order By: Relevance
“…Teaching PE at a distance is very challenging due to the different material requirements of teachers and students, lack of props, difficult direct demonstrations, lack of feedback, and last but not least, student safety (Friskawati, 2021;Hambali et al, 2020;Marshall et al, 2020;Park, 2021). Therefore, only some methods are suitable for distance education, especially when younger students are involved, as distance education represented both an overcoming of physical distance and an unimaginable obstacle to learning, forcing primary school teachers to be even more versatile and flexible (DeCoito & Estaiteyeh, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Teaching PE at a distance is very challenging due to the different material requirements of teachers and students, lack of props, difficult direct demonstrations, lack of feedback, and last but not least, student safety (Friskawati, 2021;Hambali et al, 2020;Marshall et al, 2020;Park, 2021). Therefore, only some methods are suitable for distance education, especially when younger students are involved, as distance education represented both an overcoming of physical distance and an unimaginable obstacle to learning, forcing primary school teachers to be even more versatile and flexible (DeCoito & Estaiteyeh, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Distance education in PE is otherwise possible but at the same time there are many shortcomings such as lack of feedback from teachers, lack of motivation and encouragement from students, lack of time to present materials for distance education, inconsistencies between teachers' and students' expectations regarding the performance of assigned tasks and the like (Friskawati, 2021). Similarly, Hambali et al (2020) suggest that the reasons for less effective distance education in PE are that PE is a very hands-on process, students need immediate and instant feedback on the success of the movement, distance education that requires mutual cooperation among participants (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies report that physical activity carried out in the school environment is physical activity to promote a healthy lifestyle such as walking, jogging, gymnastics and swimming. However, this does not have an impact on the physical activity carried out after the learning activities are completed where students tend to have low physical activity after leaving the school environment (Friskawati, 2021). In addition, we also found that the home environment has a significant impact on behaviour not to carry out physical activities outside the school environment (S et al, 2020), in addition, we have also found that many studies have been conducted using standard tools, assessments and validations.…”
Section: Discussionmentioning
confidence: 99%
“…It complements formal education by supporting lifelong education, such as Islamic boarding schools. (Friskawati, 2021;Syafei et al, 2021) Islamic boarding schools are traditional schools where students live and study together under the guidance of a Kiai.…”
Section: Introductionmentioning
confidence: 99%